THE RELATIONSHIP BETWEEN JOINT PAIN AND SLEEP QUALITY AMONG OLDER ADULTS AT LKS-LU PANGESTI LAWANG - Sisillia Caroline Sugiarto; Febrina Secsaria Handini; Ellia Ariesti (Jurnal Ilmiah Keperawatan, 2026)
Background: Older adults are vulnerable to age-related musculoskeletal changes that may cause joint pain and sleep disturbances. Persistent sleep problems can affect physical and psychological health and quality of life. Research on joint pain and sleep quality among older adults in nursing homes remains limited. Purpose: This study aimed to determine the relationship between joint pain and sleep quality among older adults at LKS-LU Pangesti Lawang. Methods: This quantitative correlational study used a cross-sectional design involving 40 older adults selected through total sampling. Joint pain was measured using the Pain, Enjoyment of Life, and General Activity (PEG) Scale, and sleep quality using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using univariate analysis and Spearman’s rho test at α = 0.05. Results: Among 40 respondents, 18 (45.0%) experienced moderate joint pain, 15 (37.5%) severe pain, and 7 (17.5%) mild pain. Most respondents had poor sleep quality (33; 82.5%). Spearman’s rho showed a significant relationship between joint pain and sleep quality (p = 0.001; r = 0.714), indicating a strong positive correlation. Conclusion: Higher joint pain was associated with poorer sleep quality among older adults. Comprehensive pain and sleep assessment and non-pharmacological pain management may help improve sleep quality.